Realisasi Tokoh Kaluna dalam Film Home Sweet Loan pada Kehidupan Nyata menggunakan Teori Psikologi Sastra - Afifah, Fadhilah Nur; M, Majidah; Wafa, Najahatul; Neina, Qurrota Ayu (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research examines the Realization of Kaluna’s Character in the Home Sweet Loan Film in Real Life using Literary Psychology Theory through a qualitative approach. This film tells the story of Kaluna’s struggle to realize her dream of owning her own home but she must face economic problems, family problems and toxic relationships. This research aims to explain the realization of kaluna’s character in real life such as family and romance problems, economic problems, being the backbone of the family, burying dreams. This research uses Abraham Maslow’s theory. The results of this study are that in the movie Home Sweet Loan there are several scenes which show symptoms of literary psychology. Then in this study found several solutions based on questionnaires that have been distributed to respondents.